PERSEPSI TERHADAP PELAYANAN OPERASI LASIK DI RUMAH SAKIT MATA MASYARAKAT JAWA TIMUR - Elly Ratnaningsih (UNUSA Press, 2018)
Visiting of lasik surgery patients at Eye Hospital of East Java in 2016 is quite low (9%) whilein 2017 increased (10%) but still below target. Such low achievements are likely to be influenced byconsumer perceptions of lasik surgery services. This study aims to assess the community perceptionof lasik surgery services Eye Hospital of East Java. Assessment of perception includes price, people,process and physical evidence. This study shows that respondents' perceptions of lasik surgery ratesare cheaper than those in other hospitals. Overall perception of officers and service process lasiksurgery is good. While the perception of respondents to the physical appearance has not been good,because respondents feel not satisfied with hospital facilities. This research recommends innovationin marketing efforts lasik surgery service and hospital management need to improve infrastructurefacilities.